Cationic Cellulose Nanocrystals: Synthesis, Characterization and Cytotoxicity Studies. Issue 1718 (2015) - Sunasee, Rajesh; Hemraz, Usha D.; Ckless, Karina; Burdick, James S.; Boluk, Yaman
ABSTRACT: Cellulose nanocrystals (CNCs) have emerged as a new class of renewable material for various applications due to their remarkable properties and commercialization prospect. The relative low density, expected low cost, non-toxic character, uniform nanosize distribution, high aspect ratios, high surface area, thermal properties and high modulus of elasticity make CNCs attractive nanomaterials that recently prompted the industrial production of CNCs in North America. Surface functionalization of CNCs continues to be an exciting area of research for the design of novel CNC-based materials. In this work, we report the synthesis, characterization and cytotoxicity studies of novel cationic surface modified CNC derivatives. The negative surface of CNC was rendered positive after grafting with cationic polymers via surface-initiated living radical polymerization method. The modified CNCs were characterized by both spectroscopic and microscopic techniques. Their cytotoxicity effects were evaluated using MTT assay in two cell lines such as mouse macrophages (J774.A1) and human breast cancer (MCF7). Preliminary studies indicated that only one of the modified CNCs caused significant decrease in J774.A1 cell viability (50%), at the highest concentration tested (100 µg/mL). However this concentration is well above of what would be applicable for biomedical purposes. MCF7 cells were not affected by any of the cationic CNCs at any concentration. A detailed cytotoxicity study is currently underway to fully understand the interaction of these cationic CNCs with the biological systems for possible bio-inspired applications.